P550 Characterisation of hospitalised patients with ulcerative colitis treated with tofacitinib in the OCTAVE clinical programme for up to 7.8 years. (30th January 2023) - Taxonera, C; Ha, C; del Pilar Fortes, M; Gardiner, S; Mundayat, R; Ghosh, S; Connor, S J
Abstract: Background: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). Efficacy and safety of tofacitinib were demonstrated in the OCTAVE clinical programme. 1, 2 Here, we present an analysis of the number and causes of UC-related hospitalisations during the OCTAVE clinical programme. Methods: This descriptive analysis comprised patients (pts) hospitalised for UC who received placebo or tofacitinib 10 mg twice daily (BID) in OCTAVE Induction 1&2 (NCT01465763; NCT01458951) 1, and pts who received placebo, or tofacitinib 5 or 10 mg BID in OCTAVE Sustain (NCT01458574) 1, or ≥1 dose of tofacitinib in OCTAVE Open (NCT01470612) 2 ; it includes data from pts with ≤7.8 years of tofacitinib exposure. We examined the demographic and clinical characteristics, proportions, causes and other aspects of UC-related hospitalisations in pts treated with placebo or tofacitinib in the OCTAVE clinical programme. Results: Overall, 1139 pts with UC were included in this analysis. Demographic and disease characteristics of pts with UC-related hospitalisations were generally similar across treatment groups in each study; most pts were <40 years old, had pancolitis, a mean total Mayo score >8, prior treatment with oral corticosteroids and immunosuppressants (Table 1). Ninety-five pts had UC-related hospitalisations; of whom 92 had one UC-related hospitalisation and 3 pts were hospitalised twice (Table 2). In OCTAVE Induction 1&2, OCTAVE Sustain and OCTAVE Open, 2.1%, 1.0% and 6.6% of pts, respectively, had UC-related hospitalisations with tofacitinib 10 mg BID vs 1.0% and 2.9% of pts receiving tofacitinib 5 mg BID in OCTAVE Sustain and OCTAVE Open, and 3.4% and 4.0% of pts receiving placebo in OCTAVE Induction 1&2 and OCTAVE Sustain, respectively. UC-related hospitalisations did not lead to temporary treatment discontinuations in most pts (Table 2). The most frequent cause of UC-related hospitalisations in tofacitinib- and placebo-treated pts was non-surgical UC-related events (ie, UC flares; Table 2). Conclusion: UC-related hospitalisations were infrequent in the OCTAVE clinical programme, and rates were generally lower than those reported in a real-world assessment of pts with UC treated with biological therapies. 3 Most hospitalised pts were aged <40 years with severe disease and prior corticosteroid and immunosuppressant exposure. The most common cause of hospitalisation was non-surgical UC-related events. References: 1. Sandborn WJ et al. N Engl J Med 2017;376:1723-1736. 2. Sandborn WJ et al. Aliment Pharmacol Ther 2022;55:464-478. 3. Bressler B et al. J Crohn's Colitis 2021;15:1694-1706.